2002
DOI: 10.1182/blood-2002-01-0151
|View full text |Cite
|
Sign up to set email alerts
|

Bay 11-7082 inhibits transcription factor NF-kappa B and induces apoptosis of HTLV-I-infected T-cell lines and primary adult T-cell leukemia cells

Abstract: Human T-cell leukemia virus type I (HTLV-I IntroductionAdult T-cell leukemia (ATL) is an aggressive malignancy of CD4 ϩ T cells, and its development is closely associated with human T-cell leukemia virus type I (HTLV-I) infection. [1][2][3] In vitro, HTLV-I transforms primary human CD4 ϩ T cells in interleukin-2 (IL-2)-dependent and IL-2-independent manners. Although the mechanism of transformation and leukemogenesis is not fully elucidated, there is evidence to suggest that the viral Tax protein plays a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(216 citation statements)
references
References 54 publications
8
208
0
Order By: Relevance
“…We reported previously that Bay 11-7082, an NF-jB inhibitor, blocked constitutive NF-jB activation and induced apoptosis of HTLV-1-infected T-cells. 40 Here, we found that treatment with Aurora kinase inhibitor suppressed constitutively activated NF-jB signaling in HTLV-1-infected T-cell lines. Knockdown of Aurora A reduced phosphorylation of IKKb, but not IKKa or IKKg (data not shown).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We reported previously that Bay 11-7082, an NF-jB inhibitor, blocked constitutive NF-jB activation and induced apoptosis of HTLV-1-infected T-cells. 40 Here, we found that treatment with Aurora kinase inhibitor suppressed constitutively activated NF-jB signaling in HTLV-1-infected T-cell lines. Knockdown of Aurora A reduced phosphorylation of IKKb, but not IKKa or IKKg (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…This is important because constitutively activated NF-jB signaling plays important roles in the growth and survival of HTLV-1-infected T cells. 36,40 Aurora A siRNA reduced phosphorylation of IKKb, but not that of IKKa and IKKg, without affecting Tax expression in HUT-102 cells (Fig. 3b and data not shown).…”
Section: Knockdown Of Aurora a Suppresses Cell Growth And Nf-jb Signamentioning
confidence: 76%
“…[44][45][46] Inhibition of NF-kB signaling resulted in apoptosis and decreased Bcl-x L expression in HTLV-I-infected T-cell lines and primary ATL cells. 47 In our study, we investigated the relationship between HTLV-I and ATL with respect to the induction of resistance to apoptosis in T-cells mediated by HTLV-I Tax. As reported previously, 19 NF-kB nuclear translocation was stimulated in Tax-transfected CTLL-2 cells in the absence of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Tax activation of NF-B is required for immortalization of T lymphocytes (4). Further, pharmacologic inhibition of NF-B leads to apoptosis of HTLV-1 transformed T cell lines and ATL cells (5).…”
mentioning
confidence: 99%